A central limit theorem for correlated variables with limited normal or gamma distributions. Issue 21 (2nd November 2019) - DeRiggi, Dennis
Abstract: Non-negative limited normal or gamma distributed random variables are commonly used to model physical phenomenon such as the concentration of compounds within gaseous clouds. This paper demonstrates that when a collection of random variables with limited normal or gamma distributions represents a stationary process for which the underlying variables have exponentially decreasing correlations, then a central limit theorem applies to the correlated random variables.